2019
DOI: 10.3390/ijms20215292
|View full text |Cite
|
Sign up to set email alerts
|

SASP-Dependent Interactions between Senescent Cells and Platelets Modulate Migration and Invasion of Cancer Cells

Abstract: Alterations in platelet aggregation are common in aging individuals and in the context of age-related pathologies such as cancer. So far, however, the effects of senescent cells on platelets have not been explored. In addition to serving as a barrier to tumor progression, cellular senescence can contribute to remodeling tissue microenvironments through the capacity of senescent cells to synthesize and secrete a plethora of bioactive factors, a feature referred to as the senescence-associated secretory phenotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 80 publications
0
11
0
Order By: Relevance
“…To the best of our knowledge, no studies about senescent TC cells and CAFs are currently available. Some studies have assessed the interactions between senescent cells and other cell types as platelets [20] and immune cells [21]. In addition, our laboratory has recently described an interplay between senescent thyrocytes and macrophages [22].…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, no studies about senescent TC cells and CAFs are currently available. Some studies have assessed the interactions between senescent cells and other cell types as platelets [20] and immune cells [21]. In addition, our laboratory has recently described an interplay between senescent thyrocytes and macrophages [22].…”
Section: Discussionmentioning
confidence: 99%
“…First described in human primary cells subjected to long-term culture [14], a similar phenotype can be triggered prematurely in response to various forms of stress, including genotoxic, oxidative, oncogenic and therapeutic stress [15]. Indeed, several anticancer drugs are capable of inducing cellular senescence in cancer cells, including conventional chemotherapeutic drugs (i.e., Doxorubicin) [16] and more recently developed CDK4/6 inhibitors [17,18]. Importantly, cellular senescence has also been described in developmental contexts, in the absence of stressful stimuli [19][20][21], and senescent cells accumulate in aging tissues and sites of tissue damage [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Nie et al [46] showed that expression of a large number of monocytes can inhibit the immune response of T cells near the tumor and promote immune escape of cancer cells by increasing cyclo-oxygenase-2 expression. Senescence-associated secretory phenotype interaction between platelets also plays an important role in metastasis and invasion of cancer cells [47]. Tumor occurrence, development and metastasis lead to changes in immune cells and in ammation in the tumor microenvironment, which would affect the circulating immune cells with disease progression.…”
Section: Discussionmentioning
confidence: 99%